Isolation and Identification of Fungi from Peanut Samples Sold at Adama City Markets, Oromia Regional State, Ethiopia - Temesgen, Tseday; Chala, Bayissa (International Journal of Scientific Research in Biological Sciences, 2020)
Peanut is a legume crop that belongs to the family of Fabaceae, genus Arachis, and botanically named as Arachis hypogaea. Peanuts have been consumed in a variety ways in Adama city perhaps with poor hygiene condition. The major consumers of peanuts in Adama are Khat chewers and people who may consume roasted barely grain with nuts. Fungal contamination associated with peanut seeds sold at Adama city markets and streets were examined in the present study. Examination was performed depending on the morphological features of the fungal genera. Potato dextrose agar (PDA) was prepared and autoclaved at 121oC for 15min. Peanut seeds were surface sterilized with 70% alcohol and rinsed with water and plated in the petri dish containing PDA. Incubation temperature was 25oC and the fungal growth were observed for 5 days. The isolated fungi were then sub cultured on another prepared PDA and used for identification. From the observed growth features and color of the fungal colonies, four taxa of fungi were examined and those were Aspergillus species, Penicillium species, Fusarium species and Mucor species. The study revealed that almost all the 225 peanut samples were infected by one of the four fungal genera. Aspergillus species were identified to be the most prevalent isolates with a percentage of 45.5% followed by Penicillium (32.9%). The rest Fusarium species and Mucor species were the least prevalent with proportion of 10.9% and 10.5%, respectively. The hot and arid climate of the city appears to be one main reason for the acceleration of the fungal growth in peanut. Further surveillance and setting regulation by the government on seed pathogens will play a great role in reduction of those fungi.